A Tgfbr1/Snai1-dependent developmental module at the core of vertebrate axial elongation - Dias, André (2021)
LISBOA-01?0145-FEDER-030254 SCML-MC-60-2014 LISBOA-01-0145-FEDER-022170 PD/BD/128426/2017 PD/BD/128437/2017 MR/S008799/1 MR/ K011200/1 DEV-170806